IMPROVING STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE TEXTS THROUGH COGNITIVE STRATEGY AT GRADE VII-2 OF SMPN 1 INDRA PRAJA TEMBILAHAN - Fauzul Etfita (Fakultas Bahasa dan Seni UNP, 2014)
PERBAIKAN KEMAMPUAN SISWA DALAM MEMBACA TEKS DESKRIPTIF MELALUI STRATEGI KOGNITIF DI KELAS VII-2 DI SMPN 1 INDRA PRAJA TEMBILAHANAbstractThis study aimed at determining whether cognitive strategy can improve students' skills in writing descriptive texts, as well as the factors that influence the improvement of writing skills. This research is a classroom action research conducted in two cycles. Each cycle consists of four sessions. Each consists of a plan, action, observation, and reflection. Participants in this study were all students of grade VII-2 SMPN1 Indra Praja Tembilahan amounting to 22 students. The data were collected through: (1) observation sheets; students, teachers, teaching step (2) field notes (3) interviews, and (4) the writing test. The study found that the use of cognitive strategy can improve students' skills in writing descriptive text. The findings of this study indicate that an increase in the average value of students above the minimum completeness criteria namely 75 for English subject. The factors that influence students' skills in writing the descriptive text are (a) reading material provided to students, (b) students’ motivation, and (c) teachers’ approach toward the student. It can be concluded that the application of cognitive strategy on teaching reading descriptive text can give positive results with increasing students' skills in reading the descriptive text. AbstrakPenelitian ini bertujuan untuk mengetahui apakah cognitive strategy dapat meningkatkan keterampilan siswa dalam menulis teks descriptive, serta factor-faktor apa saja yang mempengaruhi peningkatan keterampilan menulis tersebut. Penelitian ini adalah penelitian tindakan kelas yang dilaksanakan dalam dua siklus. Setiap siklus terdiri dari empat kali pertemuan. Masing-masing terdiri dari plan, action, observation, dan reflection. Partisipan pada penelitian ini adalah seluruh siswa kelas VII-2 SMPN 1 Indra Praja Tembilahan yang berjumlah 22 siswa. Data penelitian ini dikumpulkan melalui: (1) lembar observasi; siswa, guru, langkah mengajar (2) catatan lapangan (3) wawancara, dan (4) tes menulis. Penelitian ini menemukan bahwa penggunaan cognitive strategy dapat meningkatkan keterampilan siswa dalam menulis teks descriptive. Temuan penelitian ini menunjukkan bahwa terjadi peningkatan nilai rata-rata siswa diatas kriteria ketuntasan minimal mata pelajaran bahasa inggris yaitu 75. Adapun faktor-faktor yang mempengaruhi keterampilan siswa dalam menulis teks descriptive adalah (a) bahan bacaan yang diberikan kepada siswa, (b) motivasi siswa, dan (c) pendekatan guru terhadap siswa. Maka dapat disimpulkan bahwa penerapan cognitive strategy pada pengajaran membaca teks descriptive dapat memberikan hasil yang positif dengan meningkatnya keterampilan siswa dalam membaca teks descriptive.Keywords: Students’ reading Comprehension of Descriptive text, cognitive strategy